مقارنة استخدام وسيلة جوجل فرام وزوهو فرام لوسيلة تعليم اللغة العربية - M. Rizal Rizqi (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2022)
The Google form is a Google product that is used to create a review and questionnaire paper across the web and to collect the response. Zoho Form is a web-based online platform used free of charge to create an online questionnaire and to collect a response. Google Form is used for the online form that is placed on the Internet or released in social media. Zoho Form's platform is easy to apply to users via computer, laptop or phone at any time and place with an Internet connection. The advantages of the Google Form platform are as follows: the industry is easy and effective use, and the shape of Beidou is attractive, this application provides facilitations for users to enter and use their images or logos in the browser, and the user does not need to print the earrings for Google Form and Majna, and lack of time to share. The disadvantages of the Google Form platform are that it is designed limitedly. One is the lack of character types, it requires a lot of internet quota, you must have email, and you can't send voice messages. The use comparison between them is that the Google Form platform is a tool that is used to plan the program, to send a note, to gather news, to give questions, and so on. The Google Form platform is used for the online form that is placed in the Internet where twenty-three programs are available. Zoho Form is the web-based electronic platform with twenty-seven programs available, and from the application axis it comes in two types; - application by computer - and application by phone. From here the use was becoming easy for users because it is not limited to the constraint of time and place, the Google Form platform does not have the presence detection, and the Zoho Form platform has no presence detection, the Google Form platform does not contain sending voice messages, while the Zoho Form platform contains sending voice messages, and can be used for companies, bodies and associations by applying the programs available in it such as sales, marketing, calculations and others